Components of the Educational Management Information System (Komponen Sistem Informasi Manajemen Pendidikan) - Aditya Bayu; Farhan (Lentera Pendidikan: Jurnal Ilmu Pendidikan dan Keguruan Islam, 2025)
The development of Information Systems has made information a primary necessity while also transforming the role of managers in organizational management. With advances in information technology, operational activities have become more accurate and timely, enabling managers to analyze their performance more easily. Initially, Management Information Systems (MIS) did not involve technology, but over time, MIS has become inseparable from technology. MIS has increasingly garnered attention, especially in the fields of education and business.  One of the main components in operating an information system is human resources, or brainware. Brainware plays a crucial role as the designer, operator, and user of computer systems and is responsible for managing hardware and software to produce the required information. The concept of a computer as a unified system consists of three inseparable elements: hardware, software, and brainware, which support each other. Without any of these elements, the system cannot function optimally. Management Information Systems integrate their components to provide relevant and timely information. This information comprises processed data that supports decision-making and achieving organizational goals. Generally, information systems include communication, routine transactions, management, and information required by an organization’s internal and external parties.